-6x-21+9x=42

Simple and best practice solution for -6x-21+9x=42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x-21+9x=42 equation:


Simplifying
-6x + -21 + 9x = 42

Reorder the terms:
-21 + -6x + 9x = 42

Combine like terms: -6x + 9x = 3x
-21 + 3x = 42

Solving
-21 + 3x = 42

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '21' to each side of the equation.
-21 + 21 + 3x = 42 + 21

Combine like terms: -21 + 21 = 0
0 + 3x = 42 + 21
3x = 42 + 21

Combine like terms: 42 + 21 = 63
3x = 63

Divide each side by '3'.
x = 21

Simplifying
x = 21

See similar equations:

| 2x+6=-7x-9 | | 27-(x+9)=4x-2 | | 6x-(2x+4)-(x+3)= | | 7(2y+1)=2(y-13) | | 0.4=0.75+y | | -6b+5(1-b)=-8b+26 | | (2x-1)(x^2-3x+5)=0 | | 3(2x+1)+1+2x=3(2x+2)+x | | 2X^2-16X+64= | | 7y-9-4y+4=0 | | 1.2x=40.8 | | 0(2x-4)^-11/2 | | -5+x-9=15 | | -1/4a7/4a=-21 | | 3/5x-3=2.25 | | 0.4=0.75y | | -(-5-6n)-3(2n+3)=3 | | 3x+4=-2x-14 | | -12-1x=8-3x | | 5x-3y=10fory | | -6=m+(-25) | | 3x/4=2 | | 1.8q-4.3-2.3q=-1.5q-4.6 | | -6=my+(-25) | | 7x^2-21x+0=0 | | X+8+7=2x+15 | | 108=-4(-6x-3) | | -20=5+x | | 5x/6=0 | | 3(x+1)+1+2x=3(2x+2)+x | | -7(-4n-4)+2(n+5)=-22 | | (25x)/45=-65 |

Equations solver categories